2021
DOI: 10.1111/bjet.13066
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a group awareness tool on knowledge construction in computer‐supported collaborative learning

Abstract: The present study attempts to examine the effects of group awareness on knowledge construction and further surveys in what ways the different group awareness types support the collaboration in CSCL.| 1179 EFFECT OF A GA TOOL ON KNOWLEDGE CONSTRUCTION IN COMPUTER IN CSCL

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…On the contrary, synchronized physiological arousal occurred the least under motivational challenges. This result could be explained by previous findings that the unequal participation of team members is often overlooked because students are more concerned with completing tasks rather than other members’ engagement ( Li et al, 2021 ). This finding extends previous research by further indicating that this disregard can also be reflected in students’ physiological signals as members showed the least synchronized physiological response to motivational challenges.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…On the contrary, synchronized physiological arousal occurred the least under motivational challenges. This result could be explained by previous findings that the unequal participation of team members is often overlooked because students are more concerned with completing tasks rather than other members’ engagement ( Li et al, 2021 ). This finding extends previous research by further indicating that this disregard can also be reflected in students’ physiological signals as members showed the least synchronized physiological response to motivational challenges.…”
Section: Discussionmentioning
confidence: 84%
“…Therefore, scripts or awareness tools are needed to help students better identify challenges and become more aware of their occurrence to respond to and regulate them promptly. In addition, the least synchronized physiological arousal under the motivation challenge should attract educators’ notice for the reason that this disregard for equal participation could lead to poor group performance in the long term ( Li et al, 2021 ). Instructional intervention, such as directly emphasizing the value of equal participation, should be implemented to guide students to pay more attention to group members’ engagement.…”
Section: Conclusion and Pedagogical Implicationsmentioning
confidence: 99%
“…In addition, Moon and Ke ( 2020 ) adopted game-based learning to enhance learning engagement and found that the types of learners’ in-game actions promoted differential learning engagement. Furthermore, previous studies have explored learning engagement from various perspectives, such as the factors influencing learning engagement (Yun et al, 2020 ), the promotion of learning engagement by blogs, mobile learning and assessment tools (Bedenlier et al, 2020 ), and methods for measurement of individual learning engagement (Li et al, 2021a , b , c ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Within GA literature, the concept itself is mostly ill-defined since tools rather than the psychological construct itself have been the focus of most of this research. If definitions are proposed, they refer to the concept as "knowledge" (e.g., Kirsch Pinheiro & Souveyet, 2018;Strauß & Rummel, 2021;Yilmaz & Yilmaz, 2020) or "knowledge and perception" (e.g., Buder & Bodemer, 2008;Erkens & Bodemer, 2019), "understanding" (e.g., Ma et al, 2020, following Dourish & Bellotti, 1992, "information" (e.g., Kirsch Pinheiro & Souveyet, 2018;Ma et al, 2020) or "information that allows to understand" (e.g., Papadopoulos et al, 2018), "(state of) being informed" (e.g., Buder et al, 2021;Cheng et al, 2021;Lin et al, 2016;Schnaubert & Bodemer, 2019following Bodemer & Dehler, 2011, "consciousness and information" (e.g., Li et al, 2021following Gross et al, 2005 or "information that is mentally present" (Bodemer et al, 2018). Thus, to describe or even define GA, researchers often use a variety of terms related to awareness, but not quite capturing all facets.…”
Section: Defining Aspects Of Group Awarenessmentioning
confidence: 99%